PENGADAAN MAKANAN BERGIZI UNTUK ANAK-ANAK DI LINGKUNGAN SEKOLAH (Studi kasus di TPQ Raudhotul Huda Wangandowo) - Rohmatul Laeli; Fatimah Azzahro; Nunung Yuliani; Muhammad Taufiq Abadi (Universitas Kristen Indonesia Toraja, 2023)
Nutrition greatly influences the growth and development of children who are still in the learning process at school. The habit of snacking on children has become a common habit and is found at various socio-economic levels of society. Snacks whose cleanliness cannot be controlled by the school and which are contaminated with dust and dirt are in great demand by school children. The purpose of this service activity is to provide socialization or learning about the importance of nutritious food for children at TPQ Raudhotul Huda Wangandowo. The method used in this service is using learning methods in the form of; the lecture method is in the form of delivering theory, the second is the discussion and question and answer method, used to test participants' understanding of the material that has been delivered. The results of this activity showed that the students at TPQ Raudhotul Huda Wangandowo were very enthusiastic in listening to the material presented by us. Some students also understand about nutritious food, it is proven that they can answer questions from us